Estudo sobre os aspectos culturais da terminologia dos contratos de prestação de serviços em língua portuguesa e língua francesa - Pandim, Gildaris Ferreira [UNESP] (2014)
This work, inserted in the scope of Terminology, aims at studying the recurrent terminology in service agreements in the language pair Portuguese (from Brazil) and French (from France). The subject matter of this legal instrument is the performance of material or intellectual services upon remuneration and can be executed between individuals and legal entities. Regarding the General Terminolgy, we relied on the theoretical frameworks developed by Barros (2004, 2007), Depecker (1999, 2002, 2005) and Rey (1979, 1988, 2007). Also, with respect to the Bilingual Terminology, we based ourselves on the researches developed by Barros and Silva (2005), Depecker (2002) and Dubuc (2002). Finally, the study on cultural factors has been based on the works from Boulanger (1995), Diki-kidiri (1998, 2007, 2008), Gambier (1987), Gaudin (1991, 1993, 2003, 2007) and Guespin (1985). The research was carried out based on two study corpora, comprised of agreements originally drafted in Portuguese (CPSP) and by agreements originally drafted in French (CPSF). The collection of the corpora followed specific criteria related to language, to the environment (writing documents), to gender (professional and specialized), to the authorship and to the date and place of publication, and the agreements comprising the corpora have been gathered from several sources: virtual especially (websites of companies, law firms, accounting firms), a Brazilian law firm, a French law firm and a French-Brazilian law firm. From the perspective of terminological studies, terminology found in service agreements consist of simple terms, complex terms, compound terms, brachygraphic forms (abbreviations and acronyms). Once they are legal instruments, service agreements contain many terms arising from the legal field. From the interlinguistic perspective, a large part of the terms (80%) has counterparts in the language pair Portuguese-French with similar concept, ...